Chemistry and chemists in Florence : from the last of the Medici family to the European Magnetic Resonance Center /: from the last of the Medici family to the European Magnetic Resonance Center. (2016) - Fontani, Marco, 1969-; Orna, Mary Virginia; Costa, Mariagrazia
No abstract available